Comparing Mohs micrographic surgery and wide local excision in the management of head and neck dermatofibrosarcoma protuberans: a scoping review (2024)
ABSTRACT: Dermatofibrosarcoma protuberans (DFSP) is a rare, locally aggressive cutaneous sarcoma with a propensity for recurrence. Its management, particularly in the head and neck (H&N) region, presents unique challenges. This study aimed to evaluate the effectiveness of Mohs micrographic surgery (MMS) compared to wide local excision (WLE) in treating H&N DFSP and its impact on recurrence rates and tissue preservation. A comprehensive search was conducted in PubMed/MEDLINE, yielding 29 relevant studies. We included studies comparing MMS and WLE in adult patients with H&N DFSP and reporting local recurrence outcomes. Data were analyzed using random effects analysis, with a meta-analysis performed for comparative studies. Analysis of studies demonstrated a lower recurrence for MMS. Comparative analysis of five studies involving 117 patients showed a significantly lower recurrence rate in the MMS group (2%) compared to the WLE group (19%). Margin status varied between studies, with some achieving negative margins at shorter distances. In the management of H&N DFSP, MMS has emerged as a superior surgical technique, consistently associated with reduced recurrence rates and the potential for tissue preservation. The adoption of MMS should be considered for its capacity to achieve negative margins with fewer processing steps, particularly in anatomically complex regions like the H&N.